MENAKAR TEOLOGI KEADILAN DALAM POLIGAMI - Subehan Khalik (Universitas Islam Negeri Alauddin Makassar, 2019)
As a law passed by God, polygamy has transedental elements that often cause various interpretations. In this context, polygamy creates a new atmosphere for restoring the values of justice in its practice of law. If men are responsible for their actions as per the Qadariyah group's thinking, then polygamy should provide justice for women. However, if polygamy means the prerogative of God to bring down the law, then the demands of justice in this act cannot be brought forward because the law has become the absolute will of God.